Physiological characteristics of cassava tolerance to prolonged drought in the tropics : Implications for breeding cultivars adapted to seasonally dry and semiarid environments - El-Sharkawy, Mabrouk A. (FapUNIFESP, 2007)
The paper summarizes research conducted at International Center for Tropical Agriculture (CIAT) on responses of cassava to extended water shortages in the field aided by modern gas-exchange and water-relation techniques as well as biochemical assays. The aim of the research was to coordinate basic and applied aspects of crop physiology into a breeding strategy with a multidisciplinary approach. Several physiological characteristics/traits and mechanisms underpinning tolerance of cassava to drought were elucidated using a large number of genotypes from the CIAT core germplasm collection grown in various locations representing ecozones where cassava is cultivated. Most notable among these characteristics are the high photosynthetic capacity of cassava leaves in favorable environments and the maintenance of reasonable rates throughout prolonged water deficits, a crucial characteristic for high and sustainable productivity. Cassava possess a tight stomatal control over leaf gas exchange that reduces water losses when plants are subjected to soil water deficits as well as to high atmospheric evaporative demands, thus protecting leaves from severe dehydration. During prolonged water deficits, cassava reduces its canopy by shedding older leaves and forming smaller new leaves leading to less light interception, another adaptive trait to drought. Though root yield is reduced (but much less than the reduction in top growth) under water stress, the crop can recover when water becomes available by rapidly forming new canopy leaves with much higher photosynthetic rates compared to unstressed crops, thus compensating for yield losses with final yields approaching those in well-watered crops. Cassava can extract slowly water from deep soils, a characteristic of paramount importance in seasonally dry and semiarid environments where deeply stored water needs to be tapped. Screening large accessions under seasonally dry and semiarid environments showed that yield is significantly correlated with upper canopy leaf photosynthetic rates, and the association was attributed mainly to nonstomatal (anatomical/biochemical) factors. Parental materials with both high yields and photosynthetic rates were identified for incorporation into breeding and selection programs for cultivars adapted to prolonged drought coupled with high temperatures and dry air, conditions that might be further aggravated by global climate changes in tropical regions.